Comprehensive Analysis of Ferroptosis Regulators in Lung Adenocarcinomas Identifies Prognostic and Immunotherapy-Related Biomarkers - Sun, Sijin; Guo, Wei; Lv, Fang; Zhang, Guochao; Wang, Juhong; Li, Renda; Tan, Fengwei; Li, Ning; Xue, Qi; Gao, Yibo; Gao, Shugeng; He, Jie (Frontiers in Molecular Biosciences, 2021)
Ferroptosis is a newly discovered type of programmed cell death that differs from canonical apoptosis. However, the potential role of ferroptosis in lung adenocarcinoma (LUAD) has not been elaborated. In total, 1328 samples from databases and 36 ferroptosis regulators were included in this study. By combining random survival forest and principal component analysis algorithms, a robust prognostic ferroptosis-related risk score (FRRS) was constructed, and the performance was validated in three independent datasets. Based on the median risk score, two subgroups were identified. Then, comparisons, including of mutational profiles, functional enrichment analyses and immune components, were conducted between subgroups. An immunotherapy cohort was applied to explore potential therapeutic-related biomarkers. Finally, the clinical utility of FRRS was validated in a proteomic cohort. In the TCGA-LUAD cohort, FRRS was calculated using the expression of 11 selected genes, and patients with high FRRS had a significantly (P < 0.001) worse prognosis than those with low FRRS. Multivariate regression suggested that FRRS was an independent prognostic factor. Functional enrichment analysis indicated that FRRS was mainly involved in cell cycle, metabolic and immune-related pathways. Furthermore, FRRS was shown to be significantly (P < 0.001) associated with the abundance of CD8 T cells and tumor mutation burden (TMB). The combination of TMB and FANCD2 expression, the main contributor to FRRS, substantially increased the precision of predicting the therapeutic response. In conclusion, the present study revealed the potential role of ferroptosis regulators in LUAD and identified ferroptosis-related biomarkers for prognostic and immunotherapeutic predictions.